Community-Based Public Art and Gentrification in the Downtown Eastside of Vancouver. Issue 1 (2nd January 2019) - Szőke, Teréz; Parizeau, Kate
Abstract : Traditional art forms and artists have been increasingly enrolled in urban revitalization projects in global cities, contributing to a desirable "creative city" vibe that can lead to the displacement of existing residents. Community-based public art, however, has been seen as a form of grassroots expression and visual dissent in public spaces. This article interrogates the role of community-based public art and artists in processes of gentrification affecting the Downtown Eastside neighborhood of Vancouver, known as Canada's poorest postal code, through interviews with artists and surveys of people passing by community-based public art projects. We found that although community-based public art is an important site for critiquing urban change and social marginalization in this neighborhood, artists are constrained in their resistance to gentrification by limited funding sources for community-based public art and the growing appeal of gritty artistic urban spaces.